2020
DOI: 10.1111/fwb.13605
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and functional homogenisation of macroinvertebrate communities in recently intermittent Alpine watercourses

Abstract: 1. Mountain streams are currently shifting from perennial to intermittent regime due to the combined effect of climate change and local anthropogenic pressures. Studies on the effect of flow intermittency on macroinvertebrates are as yet inconclusive due to the large heterogeneity in geographical areas and spatial scales at which this relationship has been investigated. Given that flow intermittency is a recently documented phenomenon in the Alps, only few studies have investigated functional and taxonomical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 78 publications
(159 reference statements)
2
23
2
Order By: Relevance
“…Other studies of experimental flow reductions show that drought-affected communities shift toward more resilient smaller taxa with faster life cycles (Ledger et al, 2011;Aspin et al, 2018a), with strong dispersers replacing weak dispersers (Bogan et al, 2015), a higher proportion of lentic adapted taxa (Piano et al, 2020), and a shift in dominance toward generalists (Doretto et al, 2018). We did not find such pronounced shifts in taxonomic composition, and cursory examinations of traits yielded consistently low trait variation at all times of the study.…”
Section: Discussionsupporting
confidence: 50%
“…Other studies of experimental flow reductions show that drought-affected communities shift toward more resilient smaller taxa with faster life cycles (Ledger et al, 2011;Aspin et al, 2018a), with strong dispersers replacing weak dispersers (Bogan et al, 2015), a higher proportion of lentic adapted taxa (Piano et al, 2020), and a shift in dominance toward generalists (Doretto et al, 2018). We did not find such pronounced shifts in taxonomic composition, and cursory examinations of traits yielded consistently low trait variation at all times of the study.…”
Section: Discussionsupporting
confidence: 50%
“…Indeed, functional diversity has been recognized as an important characteristic of biological communities (Mason et al., 2005). Biodiversity loss as a consequence of ecosystem deterioration can lead to structural changes in functional niche, eventually homogenizing trait composition within the community (Brown et al., 2018; Elias et al., 2015; Piano et al., 2020). The functional aspects of recovery could be used in biomonitoring by comparing predictable changes in functional diversity along environmental gradients as well as comparing co‐occurring groups (Berger et al., 2018; Cai et al., 2019; Menezes et al., 2010; Van den Brink et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Background locations, also called pseudoabsences, are locations where presence/absence of the species is unknown, representing the range of environmental conditions in the study area. To account for potential spatial bias in species presence data due to unequal sampling effort, while providing accurate representation of environmental variations in the study area, we followed the recommendations of Barbet-Massin et al (2012) and Phillips and Dudík (2008). We selected a set of 10,000 background stream reaches in the study area, excluding the stream reaches where the Pyrenean brook newt presence is known.…”
Section: Model Settingsmentioning
confidence: 99%
“…We selected a set of 10,000 background stream reaches in the study area, excluding the stream reaches where the Pyrenean brook newt presence is known. Both background data and species occurrence records were thus biased in the same manner (Phillips & Dudík, 2008). However, the spatial bias in sampling is expected to be low, as Pottier et al (2021) suggested that the current distribution of the Pyrenean brook newt in France is now relatively well known due to huge sampling efforts since the 1990s.…”
Section: Model Settingsmentioning
confidence: 99%
See 1 more Smart Citation